Application of contactless technology on the payment cards market - Polasik, Michał; Kunkowski, Janusz (Zastosowanie technologii zbliżeniowej na rynku kart płatniczych, 2011)
The article describes the evolution and functioning of contactless technology applied to payment card systems, with particular reference to the solutions offered under the American Express-MasterCard-Visa Agreement. The benefits of contactless payments to all market participants, including card issuers, cardholders, and merchants have been discussed on the basis of results of time efficiency study. Further different strategies for implementation of contactless technology by payment card organizations as well as market achievements of most important solutions have been presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 214-226
Keywords: contactless; payment cards; RFID; NFC; EMV